2022
DOI: 10.1021/acsnano.2c05465
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy-Alloy Nanocrystal Based Macro- and Mesoporous Materials

Abstract: High-entropy-alloy (HEA) nanoparticles are attractive for several applications in catalysis and energy. Great efforts are currently devoted to establish composition–property relationships to improve catalytic activity or selectivity. Equally importantly, developing practical fabrication methods for shaping HEA-based materials into complex architectures is a key requirement for their utilization in catalysis. However, shaping nano-HEAs into hierarchical structures avoiding demixing or collapse remains a great c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
(139 reference statements)
0
12
0
Order By: Relevance
“…This suggests that here the PMMA latex is not simply a sacrificial template for inducing structuration, but plays a key chemical role for ensuring phase selectivity. Previous works from our group have shown that under an inert atmosphere, PMMA acts both as a templating and as a reducing agent, 48,49 which explains why a pure V 2 O 3 phase is obtained only for templated particles. In summary, pure monoclinic VO 2 (P2 1 /c) could be obtained only by pseudomorphic transformation with a controlled re-oxidation of the porous V 2 O 3 particles, due to the important role played by PMMA in this process.…”
Section: Resultsmentioning
confidence: 94%
“…This suggests that here the PMMA latex is not simply a sacrificial template for inducing structuration, but plays a key chemical role for ensuring phase selectivity. Previous works from our group have shown that under an inert atmosphere, PMMA acts both as a templating and as a reducing agent, 48,49 which explains why a pure V 2 O 3 phase is obtained only for templated particles. In summary, pure monoclinic VO 2 (P2 1 /c) could be obtained only by pseudomorphic transformation with a controlled re-oxidation of the porous V 2 O 3 particles, due to the important role played by PMMA in this process.…”
Section: Resultsmentioning
confidence: 94%
“…On the plus side, as obvious from the previous section, stands out the possibility to enable the design of diverse materials, hybrids, and exotic combinations. A few examples are macro and mesoporous high‐entropy‐alloy (HEA) particles ( Figure a), [ 53 ] silica‐enzyme particles (Figure 6b), [ 81 ] silicon–carbon–graphene combinations (Figure 6c), [ 79 ] iron oxide‐polymer (e.g., polylactic acid) composites (Figure 6d), [ 6 ] lipid–silica structures containing living cells (Figure 6e), [ 80 ] zeolite–enzyme–polyelectrolyte hybrids (Figure 6f), [ 60 ] LiMnO 2 –carbon black materials, [ 82 ] or iron oxide–MOF hybrids. [ 37 ]…”
Section: Spray‐drying As a Highly Versatile Tool For Materials Chemistsmentioning
confidence: 99%
“…One representative example concerns the fabrication of high entropy alloys, multi-principal element alloys, composed of five or more homogeneously mixed metals in nearly equimolar ratios. [53,95] The second advantage of fast kinetics concerns the structuration and the possibility to achieve controlled matter phase separation. Indeed the evaporation of the droplets taking place at the liquid/air interface leads to thermal and chemical gradients (solutes concentrations, surface tension, and polarity) from this interface towards the heart of the volume.…”
Section: Spray-drying: Technical Advantages and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol droplets are formed under spray, and the oxide is converted to phosphate phase in situ during high temperature and rapid heating. Jennifer et al [82] analyzed the formation mechanism of HEA nanocrystalline-based macro-and mesoporous materials and the role of templating agents by using different templating agents to synthesize HEA by spray pyrolysis. The level of chemical and structural complexity achievable by spray pyrolysis was significantly improved by fabricating HEAs-based particles with controlled porosity.…”
Section: Spray Pyrolysismentioning
confidence: 99%